(y+1)(y-2)=0

Simple and best practice solution for (y+1)(y-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y+1)(y-2)=0 equation:



(y+1)(y-2)=0
We multiply parentheses ..
(+y^2-2y+y-2)=0
We get rid of parentheses
y^2-2y+y-2=0
We add all the numbers together, and all the variables
y^2-1y-2=0
a = 1; b = -1; c = -2;
Δ = b2-4ac
Δ = -12-4·1·(-2)
Δ = 9
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{9}=3$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-1)-3}{2*1}=\frac{-2}{2} =-1 $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-1)+3}{2*1}=\frac{4}{2} =2 $

See similar equations:

| 6m–12=6m–12 | | (x-5/2)^2=0 | | 3/4^h+6=0 | | 3x(x+6)=-10 | | 3/4*h+6=0 | | 2/5p+3/4=8 | | 42+8=x | | -6p-9/3=2p+9/5 | | -0.7x+2.8=-3.14x-52 | | 3(x-4=5(3x-3) | | P+6=7/8p | | 3x+2=-(x-14)+4 | | 3x+3/4=5x+10/5 | | 37+y=32+2y= | | 7(x+5)=40+9 | | 461e-13=0 | | (x-4)²=25 | | 3x/4=5/2+2x/5 | | 3(x+2)^=2x^+3x-8 | | 2=-4.9t^2+180t | | 0.6x+4/5=0.28+1.16 | | 3(x+2)(x+2)=2x^+3x-8 | | 2/3(6x–3)=1/2(6x–4) | | 3(2x-5)-2x-2=3 | | P(x)=x-2 | | X+25+4=-43-4x-49 | | 6v+12=-6(v+2) | | 5y-6=-1 | | 0.8^n=0.2 | | 19=-2+y/3 | | x-3=(-4x+57)^1/2 | | 4x8=6x-4 |

Equations solver categories